Lifecycle dynamics and production of the calanoid copepod pseudodiaptomus in as eutrophic pond in colombo Sri Lanka - Smith, S.C. (My University, 1988)
Most of our understanding of freshwater .zooplankton ecology, 1ifecycl~s onel proeluctionis elcy'ivcel from woY'k Oil 1.(~"lr)('Y'ill.c looplilnkton populi1Lions. Surprisingly few studies describe in detail, the population dynamics of subtropicaland tropical zooplankton population dynamics; Burgis (1971) in lake George, Uganda, Wyngaard (1978) in Florida and Gophen (1978) in lake Kinneret, Israel. The conclusion appears to be that in climates that have no clearly defined seasonal cycle, zooplankton life history strategies, lifecycles, I . behaviour and composition differ markedly from thoseof temperate zooplankton. Climates that have a relatively restricted temperature range seem to favour the dominance of copepods over cladoceran species (Wyngaard, 1978) and furthermore, of a single copepod species over others (Pennak, 1957). It also appears that the reproductive efforts of tropical zooplankton may, because of fewer natural constraints, exceed those of temperate zooplankton. Some of the available literature on zooplankton lifecycles (Taylor and Slatkin, 1981; Wyngaard et al, 1982) describes a strong correlation between high temperature and short 1ifecyc 1es. Diapause (the over wintering or dormant stage) does not occur in most trop1cal zooplankton. It has been suggested that tropical species, as they are often multivoltine and are less limited by nutrient availability, tend to have higher production rates than temperate zooplankton (Gophen, 1978). This study attempts to measure the population parameters and estimate